Broncho-phonography as a method for predicting the outcome of respiratory distress syndrome in preterm infants - Ye. B. Pavlinova; T. V. Oksenchuk; L. A. Krivtsova (Бюллетень сибирской медицины)
Respiratory distress syndrome infants — the most common pathology in preterm infants, as well as the reason for the formation of such chronic lung diseases as bronchopulmonary dysplasia. Possibility of using new research techniques, such as bronchophonography to assess functional changes in the respiratory tract and predict the outcome of BPD in preterm with RDS is quite promising. The article presents the results of a prospective cohort study of comparative parameters broncho-phonography in preterm infants with respiratory distress syndrome. Using the method of logistic regression, a mathematical model to predict the risk of bronchopulmonary dysplasia in this group of children. Determined that the most common form bronchopulmonary dysplasia premature, at which the probability of occurrence greater than or equal to 50%.